Resilience Levels in The Sandwich Generation - Ade Ubaidah; Selviana Bunga Meilani; Afnisa Putri Azahra (Arbain Publishing, 2024)
The sandwich generation is a generation that is faced with the dual responsibility of caring for their children and aging parents simultaneously. Individuals who belong to the sandwich generation have burdens to bear such as having higher financial obligations and less free time. Resilience is a process of adapting well in facing difficult situations, such as trauma, accidents, threatening events or sources of stress. Therefore, the ability of resilience is important for individuals who have significant adversity, one of which is the sandwich generation. This research aims to collect and analyze articles related to the level of resilience in sandwich generation individuals. The design used is a literature review. Journals are collected using search engines such as Google Scholar. The journal criteria used are those published in 2014-2024. Based on the articles collected, it was found that the Sandwich Generation in Indonesia experienced high levels of stress due to the multiple responsibilities they carried. But they have a high level of resilience too. The sandwich generation demonstrated the ability to be resilient in the face of various obstacles. Resilience in the sandwich generation is influenced by various factors, such as personal competence, religiosity, optimism and social suppor.